The Econometrics of Joint Production: Another Approach - Griffin, James M. (The Review of Economics and Statistics, 1977)
The pseudo data approach to the joint production of petroleum refining and chemicals is described as an alternative that avoids the multicollinearity of time series data and allows a complex technology to be characterized in a statistical price possibility frontier. Intended primarily for long-range analysis, the pseudo data method can be used as a source of elasticity estimate for policy analysis. 19 references.